Confocal laser endomicroscopy for the differential diagnosis of ulcerative colitis and Crohn's disease: a pilot study - Tontini, Gian Eugenio; Mudter, Jonas; Atreya, Raja; Günther, Claudia; Zopf, Yurdagül; Wildner, Dane; Kiesslich, Ralf; Vecchi, Maurizio; Neurath, Markus; Neumann, Helmut; Vieth, Michael (Endoscopy, 2015)
The differential diagnosis of ulcerative colitis from Crohn's disease is of pivotal importance for the management of inflammatory bowel diseases, as both entities involve specific therapeutic management strategies. Confocal laser endomicroscopy (CLE) allows on-demand, in vivo characterization of architectural and cellular details during endoscopy. The aim of this study was to assess the efficacy of CLE to differentiate between ulcerative colitis and Crohn's disease.This was a prospective study involving consecutive patients with a well-established diagnosis of ulcerative colitis or Crohn's disease who underwent colonoscopy with fluorescein-aided confocal imaging.Overall, 79 patients were included (40 Crohn's disease, 39 ulcerative colitis). CLE findings in patients with Crohn's disease, showed significantly more discontinuous inflammation (87.5 % vs. 5.1 %), focal cryptitis (75.0 % vs. 12.8 %), and discontinuous crypt architectural abnormality (87.5 % vs. 10.3 %) than in ulcerative colitis (P < 0.0001). Conversely, ulcerative colitis was associated with severe, widespread crypt distortion (87.2 % vs. 17.5 % in Crohn's disease), decreased crypt density (79.5 % vs. 22.5 %), and frankly irregular surface (89.7 % vs. 17.5 %; P < 0.0001 for all comparisons). Statistically significant differences were not seen for heavy, diffuse lamina propria cell increase or mucin preservation. No granulomas were visible. Based on these findings, a CLE scoring system was developed that revealed excellent accuracy (93.7 %) when compared with the historical clinical diagnosis and the histopathological gold standard.CLE could visualize several disease-specific microscopic features, which are conventionally used in standard histopathology to differentiate between ulcerative colitis and Crohn's disease. However, because of the limited penetration depth of CLE, submucosal details or granulomas were not visible. The new scoring system may allow in vivo diagnosis of ulcerative colitis or Crohn's disease. Trial registered at ClinicalTrials.gov: NCT 02238665.
EVALuna2:2020